The Third Five Year Plan Draft Report Part I : Policy and Organisation - Planning Commission (Planning Commission, 1961)
Since Independence two main aims have guided India’s planned development - to build up, by democratic means, a rapidly expanding and technologically progressive economy and a social order which offers equal opportunity to every citizen. Large social and economic changes have already taken place, and India can look forward with assurance to sustained economic progress. As a developing economy quickens its pace and shakes off the impediments of the past, it faces new conflicts, both real and apparent, between its social, economic and other objectives. In each phase, a democratic community meets a continuing inner challenge, and must therefore re-affirm the aims it seeks and define the means by which it will reach its accepted goals in the shortest possible period.
Government of India Planning Commission